2020
DOI: 10.1021/acs.macromol.0c00190
|View full text |Cite
|
Sign up to set email alerts
|

Control of Particle Dispersion with Autophobic Dewetting in Polymer Nanocomposites

Abstract: Good particle dispersion in polymer nanocomposites (PNCs) is often hampered by autophobic dewetting where the matrix polymers are expelled from the grafted polymer, generally believed to result in increased particle aggregation and enhanced mechanical properties in dilute particle regime. However, we found that autophobic dewetting with highly extended short-chain polymers improves/disrupts particle dispersity, strongly dependent on particle volume fraction. Under strong autophobic condition given with the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Polymer-grafted nanoparticles (PGNPs) are quite promising for the manufacturing of membrane and composite materials for gas separation, biological, , mechanical reinforcement, and optical applications . Theoretical frameworks and computer simulations are very useful in guiding and interpreting experimental studies and help resolve major design issues of industrial interest. , A variety of theoretical and simulation methodologies have been employed to address systems of PGNPs and brushes, such as the polymer reference interaction site model (PRISM), self-consistent field theory (SCFT), density functional theory (DFT), molecular dynamics (MD), dissipative particle dynamics (DPD), as well as machine-learning frameworks. , In addition to these studies, scaling laws for the height of the polymer brush have been proposed to describe the structural behavior of grafted chains in the solid/polymer interfacial region over a broad range of experimental conditions. , …”
Section: Introductionmentioning
confidence: 99%
“…Polymer-grafted nanoparticles (PGNPs) are quite promising for the manufacturing of membrane and composite materials for gas separation, biological, , mechanical reinforcement, and optical applications . Theoretical frameworks and computer simulations are very useful in guiding and interpreting experimental studies and help resolve major design issues of industrial interest. , A variety of theoretical and simulation methodologies have been employed to address systems of PGNPs and brushes, such as the polymer reference interaction site model (PRISM), self-consistent field theory (SCFT), density functional theory (DFT), molecular dynamics (MD), dissipative particle dynamics (DPD), as well as machine-learning frameworks. , In addition to these studies, scaling laws for the height of the polymer brush have been proposed to describe the structural behavior of grafted chains in the solid/polymer interfacial region over a broad range of experimental conditions. , …”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, preparation of polymer‐inorganic nanocomposites has attracted lots of attention due to taking advantage of the synergistic properties of both components. Although the addition of nanoparticles obviously changes polymers properties, its degree of influence on physical properties is determined by the state of dispersion and distribution of the nanoparticles resulting from their interaction with polymer chains 6 . Many inorganic nanoparticles such as silica, 7,8 cellulose nanocrystal, 5,9 carbon nanotube (CNT), 10 nano‐clay, 11 CaCO 3, 12 and graphene 13 have been used to improve acrylic PSAs properties.…”
Section: Introductionmentioning
confidence: 99%
“…Although the addition of nanoparticles obviously changes polymers properties, its degree of influence on physical properties is determined by the state of dispersion and distribution of the nanoparticles resulting from their interaction with polymer chains. 6 Many inorganic nanoparticles such as silica, 7,8 cellulose nanocrystal, 5,9 carbon nanotube (CNT), 10 nano-clay, 11 CaCO 3, 12 and graphene 13 have been used to improve acrylic PSAs properties. The traditional method of using inorganic nanoparticles to enhance the properties of acrylic PSAs is to blend unmodified nanoparticles and the acrylic matrix.…”
mentioning
confidence: 99%
“…The immobilized layer controls the microstructure and resultant physical properties of the PNC. Many studies have been conducted to develop stable adsorbed layers by changing the chemical properties of the particles or polymers, and to elucidate the governing parameters, such as the adsorption density and sizes of the adsorbed polymers [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, particle interactions and the resulting NP structure may be altered during solvent evaporation [ 22 , 23 , 24 ]. Previous studies have shown evidence of improved NP dispersion by polymer adsorption on the NP surface in solution-casted PNC films [ 13 , 25 , 26 , 27 , 28 , 29 , 30 ]. A previous study performed by us revealed that polymer adsorption resulted in improved dispersion of NPs in PNC films, suggesting that adsorbed polymers suppress NP aggregation during drying by introducing steric repulsion between the NPs [ 31 ].…”
Section: Introductionmentioning
confidence: 99%